Identification of Halohydrins as Potential Disinfection By-Products in Treated Drinking Water. (24th November 2011) - Jobst, Karl J.; Taguchi, Vince Y.; Bowen, Richard D.; Trikoupis, Moschoula A.; Terlouw, Johan K.
Abstract : In 2001, two potential disinfection by-products (DBPs) were tentatively identified as 1-aminoxy-1-chlorobutan-2-ol (DBP-A) and its bromo analogue (DBP-B) (Taguchi 2001). Subsequently it became clear, by consulting an updated version of the NIST database, that their mass spectra are close to those of the halohydrins 4-chloro-2-methylbutan-2-ol and 3-bromo-2-methylbutan-2-ol. To establish the structures of these DBPs, additional mass spectrometric experiments, including Fourier transform ion cyclotron resonance (FTICR), were performed on treated drinking water samples and authentic halohydrin standards. It appears that DBP-A is 3-chloro-2-methylbutan-2-ol and that DBP-B is its bromo analogue. DBP-B has been detected in ozonated waters containing bromide. Our study also shows that these DBPs can be laboratory artefacts, generated by the reaction of residual chlorine in the sample with 2-methyl-2-butene, the stabilizer in the CH2 Cl2 used for extraction. This was shown by experiments using CH2 Cl2 stabilized with deuterium labelled 2-methyl-2-butene. Quenching any residual chlorine in the drinking water sample with sodium thiosulfate minimizes the formation of these artefacts.